Southeast Asian religion, culture and art of the sea - Hanafi Hussin; Santamaria, M. C. M.; Sakili, Abraham P.; Mason, Paul H. (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2013)
Expressing identity through culture and visual arts is a shared if not a nearly identical phenomenon that can be observed among the maritime communities of Southeast Asia. In Sustaining Sulu People's Identity Through Their Culture and Visual Arts, Abraham P. Sakili deals with the cultural and historical identity of the people of Sulu as suggested by or expressed through their visual arts. He primarily concentrates on the case of the Tausug. He presents an overview of Sulu history and culture in order to provide appropriate contexts for a definition of people's identity and for a discussion of features and creative processes of their representative art forms such as the ukkil (Sulu curvilinear design), textiles and mats with siyabit ("hooked-up") geometrical motifs, sunduk (gravemarker), mamaan (betel nut boxes) and a rare selection of military artifacts. He makes references to conceptual frameworks of art as cultural expression. Towards the end of his piece, he underscores the role of arts and culture in sustaining a people's identity as a positive force in the advancement of intercultural harmony, especially among the indigenous and maritime people of Southeast Asia and the world beyond as well as in devising safeguards for balance in the environment, promotion of cultural diversity in the midst of the globalized homogenizing tendencies forced by market trends.